2003
DOI: 10.1002/syn.10292
|View full text |Cite
|
Sign up to set email alerts
|

PET quantification of muscarinic cholinergic receptors with [N‐11C‐methyl]‐benztropine and application to studies of propofol‐induced unconsciousness in healthy human volunteers

Abstract: This work evaluated kinetic analysis methods for estimation of the receptor availability of the muscarinic receptor using dynamic positron emission tomography (PET) studies with [N-(11)C-methyl]-benztropine. The study also investigated the effect of propofol on central muscarinic receptor availability during general anesthesia. Six volunteers were scanned three times, once for baseline while awake, once during unconsciousness, and once after recovery to conscious level. An irreversible two-tissue compartment m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…4,7 Owing to the complex neural network in the central nervous system, it is difficult to locate precisely these cerebral target regions with traditional means, such as electroencephalography, or study of localized destruction and nerve rupture, however PET technique can provide useful information. 8 Glucose is the only source of energy for brain cells; therefore, study of cerebral glucose metabolism can be used for predicting the state of regional energy metabolism, as well as local neuronal actions. 9 As an isomer of glucose, 18 F-FDG is used as an imaging tracer for the metabolic rate of glucose because it is metabolized in the same way as glucose.…”
Section: Discussionmentioning
confidence: 99%
“…4,7 Owing to the complex neural network in the central nervous system, it is difficult to locate precisely these cerebral target regions with traditional means, such as electroencephalography, or study of localized destruction and nerve rupture, however PET technique can provide useful information. 8 Glucose is the only source of energy for brain cells; therefore, study of cerebral glucose metabolism can be used for predicting the state of regional energy metabolism, as well as local neuronal actions. 9 As an isomer of glucose, 18 F-FDG is used as an imaging tracer for the metabolic rate of glucose because it is metabolized in the same way as glucose.…”
Section: Discussionmentioning
confidence: 99%
“…A existência de uma relação direta entre a capacidade de atenção e a SH tem sido evidenciada, corroborando com a observação de hipniatras e hipnoterapeutas de que quanto maior o domínio do indivíduo sobre sua atenção, mais alta é a sua SH. Essa é uma característica pessoal e um aspecto cognitivo multidimensional que envolve perspectivas peculiares 42,109 . Parece que a condição "hipnotizada" seja caracterizada por uma dissociação funcional dos processos de monitoramento de conflitos e de controle cognitivo, envolvendo áreas do córtex frontal 1 .…”
Section: Discussionunclassified
“…Sabe-se que tal via é envolvida na atenção executiva ou de trabalho 107 . Outra consideração foi que drogas que atuam nessa via, como propofol, podem modular a atenção executiva e induzir uma experiência parecida com a hipnose 108,109 . Usando um protocolo neurofeedback, Batty et al 110 testaram a possibilidade de aumentar a SH em 30 indivíduos e elevar as taxas de teta e alfa no EEG, comparando as técnicas de RPP e auto-hipnose e verificando a importância da relação teta/alfa no aumento.…”
Section: A Hipnose E a Alteração Da Shunclassified
“…At around the same time, another group found that propofol anaesthesia was associated with a reduction in muscarinic receptor binding by the tracer [ N -11 Cmethyl]-benztropine (Xie et al 2004 ), but this fi nding was diffi cult to interpret. Although it may have indicated binding of propofol to muscarinic receptors, it could also have been the result of a change of affi nity of the receptor for benztropine or an increase in benztropine metabolism caused by propofol.…”
Section: Pet and Propofolmentioning
confidence: 95%